Implementasi In House Training (IHT) Untuk Meningkatkan Kualitas Kompetensi Pedagogik Guru SMK Negeri 1 Percut Sei Tuan Dalam Menyusun Perangkat Pembelajaran Silabus Dan RPP - Kasni Kasni (Ability: Journal of Education and Social Analysis, 2021)
This study aims to improve the quality of the Pedagogical Competence of Teachers of SMK Negeri 1 Percut Sei Tuan in Developing Syllabus and Lesson Learning Devices. The method used is the School Action Research (PTS) method. The results of the study are "To Improve the Quality of Pedagogical Competence for Teachers of SMK Negeri 1 Percut Sei Tuan in Developing Syllabus and Lesson Learning Tools" it can be concluded that: through In House Training there is an increase in pedagogical competence for teachers of SMK Negeri 1 Percut Sei Tuan. It is proven by the Syllabus and RPP learning tools made by SMK Negeri 1 Percut Sei Tuan teachers as a result of In House Training activities (examples are in the appendix) which initially there were still many shortcomings after participating in In House Training can make Syllabus and RPP learning tools completely and systematically.